Cultural and economic influences on managers’ views towards business ethics education : a comparative study of Iceland and China - Marion Christiane Ziessler 1988- (2019)
This thesis aims to test generalizability of how top managers in a cross-cultural context understand business ethics and business ethics education. Around 200 managers from two very different countries, namely Iceland and China, were approached and asked about their opinion on the current state of business ethics and how well business schools succeed in providing a solid education in ethics to their graduates, who will ultimately become the next generation of leaders and managers. The choice of countries has been made due to their strong dichotomy in terms of economic, cultural, geographical, demographical, and historical parameters. Both countries experienced the financial crash in 2008, but very differently. While Iceland belonged to the countries which were hit hardest by the crisis, China enjoyed an economic booming period at the same time. Despite great differences, similarities between the two countries are found, for instance in the development from poor, tight-knitted farming societies towards modern, developed economies and in a substantive liberation process over the last decades. However, whereas Iceland is today seen as a highly developed, modern western economy, China is still considered as a transition economy. Due to their disparate characteristics, both countries provide an interesting foundation for an empirical study on how managers with different cultural and economic backgrounds reflect on business ethics and business ethics education. The survey’s results developed three main themes. First, it appears that business ethics is more critically seen among Chinese respondents than among their Icelandic counterparts. Nevertheless, both groups perceive an improvement of business ethics and business ethics education in their country since 2008. Second, Icelandic and Chinese managers attribute business schools a central role to mandatory provide students with solid ethics education. However, this role and the effectiveness of current business ethics teaching are called into question. Even though ...